The Thyroid Gland’s Glycosylation: Aspect of Glycoprotein Function in Thyrocyte Physiology and Thyroid Disorders - Musub Saeed, Kiran Jehangir, Raisa Naz, Irfan, Ambar Shuaib, Ravi Dutt Sharma, K. Suresh Babu (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The focus of this study is on the role of glycoproteins in normal thyrocyte activity and pathologies of the thyroid. Study Design: Observational study Place and Duration: The study was carried at Pak International Medical College and Hospital from November 2021 to January 2022 Methods: There were 38 patients of both genders were presented in this study. Detailed demographics of enrolled cases included age, sex and body mass index were recorded after taking informed written consent. 19 patients had benign diffuse goiter in were included in group I and 19 (controls) patients were include in group II. Using a nonspecific proteomic strategy, such as this double difference (2D-DIGE) electrophoresis and lattice laser desorption/ionization time-of-flight masses spectrometry, we were able to determine which proteins were present in thyroid tissue (MALDI-TOF-MS). Results: Among the 92 proteins significantly different between BDG and the control group, 47 were found to be elevated and 45 were found to be lowered (1.5-fold change, ANOVA, p 0.05). Bioinformatics analysis of Ingenuity Pathway Analysis has connected the dysregulation of ERK1/2, Glutathione peroxidase, and NADPH oxidase signaling pathways to tissue damage, endocrine system dysfunction, and cancer (IPA). Conclusion: Low levels of thyroglobulin, dysregulated glycolysis, and an uptick in pro-oxidant peroxidase enzymes were found in the thyroid tissue proteome of patients with BDG. There was also a finding of dysregulation in the thyrocyte cytoskeletal proteins, redox proteins, and glycolytic pathways. Keywords: Thyroid Gland’s, Benign Diffuse Goiter, Proteins, Glycosylation